2016
DOI: 10.1152/ajpregu.00541.2015
|View full text |Cite
|
Sign up to set email alerts
|

Calibrated variability of muscle sympathetic nerve activity during graded head-up tilt in humans and its link with noradrenaline data and cardiovascular rhythms

Abstract: Muscle sympathetic nerve activity (MSNA) variability is traditionally computed through a low-pass filtering procedure that requires normalization. We proposed a new beat-to-beat MSNA variability computation that preserves dimensionality typical of an integrated neural discharge (i.e., bursts per unit of time). The calibrated MSNA (cMSNA) variability technique is contrasted with the traditional uncalibrated MSNA (ucMSNA) version. The powers of cMSNA and ucMSNA variabilities in the low-frequency (LF, from 0.04 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(77 citation statements)
references
References 33 publications
3
73
1
Order By: Relevance
“…We found that SAP-LFSD significantly increased during HUTT (Table 1, Figure 2E) and also in the seated and active standing positions (Figure 4B) compared to baseline recordings in the supine position, in line with a previous reports (Veerman et al, 1994; Barnett et al, 1999; Cooke et al, 1999; Marchi et al, 2016). On the other hand, we found that SAP-LFSD increased more modestly if at all in the supine position after blood loss (Figure 6B).…”
Section: Discussionsupporting
confidence: 91%
“…We found that SAP-LFSD significantly increased during HUTT (Table 1, Figure 2E) and also in the seated and active standing positions (Figure 4B) compared to baseline recordings in the supine position, in line with a previous reports (Veerman et al, 1994; Barnett et al, 1999; Cooke et al, 1999; Marchi et al, 2016). On the other hand, we found that SAP-LFSD increased more modestly if at all in the supine position after blood loss (Figure 6B).…”
Section: Discussionsupporting
confidence: 91%
“…three variations) that met the following prerequisites [9]: (i) the absolute value of the total MSNA burst rate variation was larger than 0 bursts · s −1 ; (ii) the absolute value of the total DAP variation was larger than 1 mm Hg; (iii) the linear correlation coefficient, r MSNA-DAP , computed in the [DAP(i), MSNA(i + τ MSNA-DAP )] plane over the correspondent MSNA burst rate and DAP sequences, was larger than 0.85, where τ MSNA-DAP represents the lag between MSNA burst rate and DAP. τ MSNA-DAP was set to 0 [9] fully in agreement with the typical latency of sBR [36,37] given the definition of MSNA burst rate variability [23]. The slope of the regression line was calculated for each sBR sequence and subsequently averaged over all sequences.…”
Section: (B) Traditional Characterization Of Cbr Via the Sequence Methodsmentioning
confidence: 99%
“…This signal represents the modulation of the MSNA burst rate, its values are expressed in bursts s −1 and has the same time resolution as the original integrated MSNA signal [23]. The HP, SAP, DAP, RM and MSNA measures were taken on a beat-to-beat basis as follows: (i) the current HP was measured as the temporal distance between two consecutive R-wave peaks detected on the ECG; (ii) the kth SAP value was taken as the maximum of AP in the kth HP; (iii) the kth DAP was computed as the minimum of the AP preceding the kth SAP; (iv) the kth RM measure was taken by sampling the RM signal at the first R-wave delimiting the kth HP; (v) the kth MSNA burst rate value was obtained by sampling the signal representing the modulation of the MSNA burst rate at the first R-wave delimiting the kth HP [23]. HP, SAP, DAP, RM and MSNA burst rate beat-to-beat variability series of N = 256 consecutive values were randomly selected within each experimental condition and linearly detrended.…”
Section: Experimental Protocol Series Extraction and Analysis Of Datmentioning
confidence: 99%
“…the tilt table inclination during graded head-up tilt test), was observed via a causal method decomposing the variance of HP series using a multivariate partial power spectral decomposition technique (Porta et al, 2012) and via a model-based conditional TE approach . The sympathetic activation and vagal withdrawal associated to the orthostatic challenge (Montano et al, 1994;Cooke et al, 1999;Furlan et al, 2000;Marchi A. et al, 2016) is likely to be responsible for the decoupling of the respiratory rhythm modulating vagal drive and HP dynamics. This decoupling is favored by the decrease of the gain of the HP-RM transfer function (Saul et al, 1991;Yana et al, 1993) and by the reduction of the RSA (Pomeranz et al, 1985) known to occur when cardiac vagal control is limited like during parasympathetic blockade performed via high dose administration of atropine.…”
Section: Effect Of the Orthostatic Challenge On Crcs In Pre Conditionmentioning
confidence: 99%